Relationship of Family Support on Self-Esteem in Patients with Breast Cancer who are Undergoing Chemotherapy - Agustin, Finna Rachma; Oktaviana, Wita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Breast cancer is one of the most common types of cancer among women worldwide. According to the prevalence of breast cancer cases in Central Java, Klaten Regency ranks first in the incidence of breast lumps in Central Java province. In the treatment process family support is considered an important factor that can affect the psychological condition of patients, including their self-esteem. The purpose of this study was to analyse the relationship between family support and self-esteem in breast cancer patients undergoing chemotherapy at Dr. Soeradji Tirtonegoro Hospital. This research method uses a quantitative approach. The research sample was selected through purposive sampling technique, which was 78 respondents. Data were collected using a questionnaire that measured the level of family support, namely the Social Response Questionnaire with the results of the validity and reliability of the Cronbach alpha results of 0.956 for 12 valid questions and self-esteem namely the Indonesian version of the Rosenberg questionnaire with the results of the validity and reliability of the Cronbach Alpha value of 0.845 with 10 valid questions. Data analysis was conducted using Pearson statistical test to determine the relationship between the two variables. The results showed that out of 78 respondents 79.5% were in the high category and 85.9% were in the high family support category and the Pearson test results showed a significant relationship between family support and self-esteem with (p<0.05) so the conclusion of this study is that there is a significant relationship in family support for breast cancer patients who are undergoing chemotherapy at Dr. Soeradji Tirtonegoro Hospital.